2020
DOI: 10.3390/su12155884
|View full text |Cite
|
Sign up to set email alerts
|

Quality Education as a Sustainable Development Goal in the Context of 2030 Agenda: Bibliometric Approach

Abstract: Quality education is understood as one of the most powerful and proven drivers for ensuring sustainable development, which can be applied in various educational contexts, formal and non-formal, and which can generate multiple benefits for the general public. Given its relevance, this article presents a bibliometric approach of the scientific production generated around Sustainable Development Goal (SPG) 4 that seeks to “Ensure inclusive and quality education for all and promote lifelong learning” as a priority… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0
4

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(29 citation statements)
references
References 47 publications
1
10
0
4
Order By: Relevance
“…The present findings are consistent with that trend, for nearly 70% of all the articles analysed were published in the last 5 years. Similar results have been reported [46,47]. Overall, they would appear to indicate that Spanish universities are exhibiting sensitivity to addressing the worldwide challenges defined by the United Nations in their research agendas.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…The present findings are consistent with that trend, for nearly 70% of all the articles analysed were published in the last 5 years. Similar results have been reported [46,47]. Overall, they would appear to indicate that Spanish universities are exhibiting sensitivity to addressing the worldwide challenges defined by the United Nations in their research agendas.…”
Section: Discussionsupporting
confidence: 89%
“…Both this study and the research conducted by González et al [47] identified Sustainability and the Journal of Cleaner Production as the publications carrying the largest share of Spanish universities' research articles on sustainability. This study found that over 37% of the papers analysed appeared in those two publications, which were found to play a significant role in disseminating more general or inter-disciplinary papers on the subject.…”
Section: Discussionmentioning
confidence: 60%
“…Específicamente el ODS4 se centra en la Educación de Calidad, la cual se entiende como uno de los motores más poderosos y probados para garantizar el desarrollo sostenible, que puede aplicarse en diversos contextos educativos, formal y no formal, y que puede generar múltiples beneficios para la población en general. Así, el ODS4 busca "Garantizar una educación inclusiva, equitativa y promover el aprendizaje permanente para todas las personas, independiente del sexo, edad, raza, etnia, vulnerabilidad y personas con discapacidades o migrantes aplicado a la educación en todos los niveles, primaria, secundaria, terciaria, formación técnica y profesional y también desde la primera infancia hasta la edad adulta (Boeren, 2019;González, Colomo & Cívico, 2020).…”
Section: Contextualización De Las Aa a Nivel Marco Global Y Marco Localunclassified
“…Revisiones bibliométricas recientes han concluido que el impacto de las publicaciones en la calidad educativa en el contexto de la Agenda 2030 y los ODS son un tema en proceso de desarrollo, con un crecimiento progresivo y continuo pero, donde aún no existen instituciones o autores que sean referencia debido a la baja producción poniendo de manifiesto la necesidad de implementar políticas a nivel global que se centren en diversas acciones relacionadas, con implicaciones tanto teóricas como prácticas (González, Colomo & Cívico, 2020).…”
Section: Pasando Al Tercer Factor Que Podría Estar Influyendo En El P...unclassified
“…Several recent studies have tackled the progress towards several SDGs and have suggested ways to achieve these goals: SDG7-clean energy [19], SDG13-climate change [20], SDG17-public private partnership [21]. Regrettably, SDG4-quality education has been relatively ignored in the literature [22] and there is not a broad corpus of knowledge on this subject [23]. Measuring the progress of ESD is of critical importance, but it faces many challenges which have largely been recognised [24,25].…”
Section: Introductionmentioning
confidence: 99%